Kinerja Ketahanan Beras Di Indonesia: Komparasi Jawa Dan Luar Jawa Periode 2005-2017 - Corryati Wardani; Jamhari Jamhari; Suhatmini Hardyastuti; Ani Suryantini (Universitas Gadjah Mada, 2019)
ABSTRACT The study analyzed rice resiliencei Indonesia using the rice security index indicator to described the performance of rice resilience by comparing Java and Outside Java condition in the period of 2005-2017. The method used was a descriptive approach, based on secondary data in the form of time series data from the Central Statistics Agency (BPS), Ministry of Agriculture (MOA), and Logistics Affairs Agency (Bulog). The data was in the form of rice production, rice consumption, rice stocks, export and import of rice and other relevant data. The study was conducted by compiling a food balance sheet and calculating the ratio of the availability of per capita rice to the consumption of per capita rice, considering the expectation of rice self-sufficiency. The results of the analysis showed that either in Java, Outside Java or at the national level, it indicated that rice production increased due to the increase of productivity, national rice consumption growth -0.0013 percent driven by per capita rice consumption growth -1.35 percent despite population growth of 1.47 percent while rice resilience grew 7.68 percent per year. Condition Outside Java had a better performance of rice resilience than Java with an increase in the relative surplus of rice availability which was 44.54 percent higher than Java. Java achieved a lower increase in rice resilience due to the lower growth in the availability of per capita rice and decreased per capita rice consumption compared to Outside Java.Optimizing of rice production Outside Java and management of community consumption patterns through means to diversified staple foods and increased the nutritional quality of consumption need to be done so that rice resilience in the future will increasedABSTRAKPenelitian mengkaji ketahanan beras di Indonesia menggunakan indikator indeks ketahanan beras untukmengambarkan kinerja ketahanan beras denganmembandingkan Jawa dan luar Jawa periode 2005-2017. Metode yang digunakan adalah pendekatan deskriptif, berdasarkan data sekunder berupa data Badan Pusat Statistik (BPS), Kementerian Pertanian (Kementan), dan Badan Urusan Logistik (Bulog), berupadata produksi padi, konsumsi beras, stok beras, ekspor dan impor beras serta data lain yang relevan. Kajian dilakukan dengan menyusun neraca bahan makanan dan menghitung rasio ketersediaan beras per kapitadengan konsumsi beras per kapita, mempertimbangkan harapan kemandirian beras. Hasil analisis regional Jawa dan luar Jawa maupun nasional menunjukkan produksi padi meningkat karena peningkatan produktivitas. Pertumbuhan konsumsi beras nasional -0,0013 persen didorongpertumbuhan konsumsi beras per kapita-1,35 persen meskipun terjadi pertumbuhan penduduk 1,47 persen, sehingga kinerja ketahanan beras tumbuh 7,68 persen per tahun.Kinerja ketahanan beras luar Jawalebih baik daripada Jawa dengan peningkatan surplus relatif ketersediaan beras lebih tinggi 44,54 persen dibanding Jawa.Peningkatan ketahanan berasJawa lebih rendah karena pertumbuhan ketersediaan beras per kapita dan penurunan konsumsi beras per kapita lebih rendah dibanding luar Jawa.Optimasi produksi beras di luar Jawa danpengelolaan pola konsumsi masyarakat melalui upaya diversifikasi pangan pokok maupun peningkatan kualitas gizi konsumsi perlu dilakukan agar ketahanan beras semakin meningkat.